THE IMPLEMENTATION OF THE STRATEGY OF (TTW) THINK-TALKWRITE IN TEACHING WRITING TO THE FIRST GRADE - Nelia Fariani Siregar (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this research is to find out the implementation of The Strategy of ThinkTalk-Write strategy in teaching writing is effective or not. The writer used descriptive textas essay text in writing. The studies used in this thesis are quantitative research andexperimental method. There are two groups, experimental and control group of classes .There are 50 student as the samples that consist of 25 students in each class and thewriter applied purposive simple. The data were collected by using test method (Pretestand Post test). The results of pretest and posttest were different. Both of the experimentaland control class. In control class, the average scores of pretest was 1025 and theaverage scores of post test was 1570. Meanwhile, in the result of pretest and posttestfrom experimental class. The average scores of pre test were 1095 and the averagescores of posttest were 2170 after the data calculation, it finds that Taccount was 5.416and Ttable. Was 2.01063 with df48 and significant level 0,05(5%). It means thatTaccount wa 5,416 and Ttable. Thus, it can be concluded that hypothesis testing in thisresearch is accepted, and the implementation of the strategy of think-talk-write strategyin teaching writing is effective to student. It can be seen from statistic calculation. It canbe concluded that the implementation of (TTW) think-talk-write in teaching writing tothe first grade at Economic Faculty, Universitas Swadaya Gunung Jati ( UGJ ) Cirebon,Jawa Barat.